The accuracy of spatial coordinates determined by trilateration method - Jonas Skeivalas; Robertas Dargis (Geodesy and Cartography, 2012)
An accuracy of spatial coordinates determined by multiple linear intersection is analysed in the paper. Such system of points determined by the method of linear intersection consists of a set of trilateration. The parametric equations are linearised using approximate coordinates of the points. The values of approximate coordinates can be determined using the method of every kind. The corrections for approximate coordinates are calculated by the least-square method. An influence of coefficients’ errors of the length of measured lines and of parametric equations for accuracy of processing equalised spatial coordinates is analysed.